Triple molybdates one-, one - and three(two)valence metals - G. E. Khaikina; S. F. Solodovnikov; O. M. Basovich; Z. A. Solodovnikova; Yu. M. Kadyrova; A. A. Savina; E. S. Zolotova; V. N. Yudin; T. S. Spiridonova (Chimica Techno Acta, 2015)
The review summarizes experimental data on the phase formation, structure and properties of new complex oxide compounds group – triple molybdates containing tetrahedral molybdate ion, two different singly charged cation, together with tri- or divalent cation. The several structural families of these compounds were distinguished and it shown that many of them are of interest as luminescent, laser, ion-conducting or nonlinear optical materials.